Prototype verification for integrated sensing and communications:current status and development trends - Jie YANG; Yixuan HUANG; Tao DU; Hang QUE; Shuqiang XIA; Shi JIN (Tongxin xuebao)
Considering the practical challenges faced by the commercialization of integrated sensing and communication (ISAC), the implementation progress and future trends of ISAC were elaborated and summarized.First, the research progress and empirical performance of single node-based ISAC prototype systems were summarized, including positioning, environmental mapping, imaging, waveform design, and beam tracking.Next, the actual gain of multi-nodes cooperation-based ISAC prototype systems in the scenarios of the Internet of vehicles and the Internet of things were analyzed.Then, focusing on cross-sensor-based ISAC prototype systems, the advantages and disadvantages of each kind of sensor and the experimental fusion performance were overviewed.Finally, the future trends in the system implementation and technical validation of ISAC were highlighted, addressing the challenges encountered in existing ISAC prototype systems.